Chronic effects of palm oil mill effluent on the hepatosomatic index of zebrafish (Danio rerio) - Zulfahmi Ilham; Setia Batubara Agung; Ali Rizwan; Wulandari Nasution Ayu; Puspita Bela; Nafis Badratun (BIO Web of Conferences)
Palm Oil Mill Effluent (POME) is a significant environmental pollutant that adversely affects fish physiology, particularly liver function, which plays a critical role in detoxification and metabolism. The hepatosomatic index (HSI) is a reliable biomarker for assessing liver health under environmental stress. This study evaluated the effects of chronic POME exposure on the HSI of zebrafish (Danio rerio) to understand their physiological adaptations to POME contamination. A Completely Randomized Design (CRD) was applied, with three treatments (0 mL/L as control, 0.5 mL/L, and 1 mL/L) and four replicates. Statistical analysis using one-way ANOVA revealed no significant differences among treatments (p > 0.05), with HSI values ranging at 0.175–0.180 by day 28. Despite fluctuations during the study, such as an initial 20% increase in HSI in treatment A by day 7, the results indicate adaptive hepatic responses without significant toxic effects at the tested concentrations. These findings highlight the resilience of zebrafish to low concentrations of POME, underscoring the importance of HSI as a biomarker for sub-lethal toxicant effects. This study contributes to aquatic pollution management by providing insights into the ecological risks associated with POME and emphasizing the need for stricter wastewater discharge standards and policies to safeguard aquatic ecosystems.